2012
DOI: 10.1007/s10900-012-9575-7
|View full text |Cite
|
Sign up to set email alerts
|

A community-based approach to disseminate health information on the hazards of prenatal mercury exposure in Brooklyn, NY

Abstract: Exposure to mercury (Hg) in utero can have neurotoxic effects on the developing fetus. Mercury exposure in women of childbearing age has been associated with frequent fish consumption, coastal proximity, foreign birth, and exposure during ritualistic practices. The aim of this study was to identify culturally-appropriate strategies to disseminate messages on the hazards of in utero Hg exposure in fertile and pregnant women in a predominantly urban immigrant community in Flatbush, Brooklyn, following findings f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…This can have different effects depending on the dose. Findings have shown that children who are exposed prenatally to high levels of MeHg can be affected in various ways, including reduced brain size; cortical blindness; motor deficiencies; impaired auditory function, language development and memory; low IQ; impaired visual-spatial abilities; and mental retardation [8][9][10][11]. These effects may become evident over the medium-or long-term and are potentially irreversible [12].…”
Section: Introductionmentioning
confidence: 99%
“…This can have different effects depending on the dose. Findings have shown that children who are exposed prenatally to high levels of MeHg can be affected in various ways, including reduced brain size; cortical blindness; motor deficiencies; impaired auditory function, language development and memory; low IQ; impaired visual-spatial abilities; and mental retardation [8][9][10][11]. These effects may become evident over the medium-or long-term and are potentially irreversible [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although the goal of effective risk communication is to provide workers with necessary information to empower them to make healthy choices, the process essentially has two steps: (a) educating the educators (e.g., occupational health and environmental health nurses and other clinicians) and (b) educating women workers of childbearing age and working parents. Because the second step cannot be achieved without accomplishing the first step, it is essential that occupational health nurses are prepared to share accurate MeHg information with workers (e.g., Anderko, 2009; Callejo & Geer, 2012; Olson, 2013).…”
Section: Nursing Implicationsmentioning
confidence: 99%
“…Environmental health nurses working with public health units are likely to develop and implement these programs. Callejo and Geer (2012) identified four ways through which communities can be made aware of in utero MeHg exposure: (a) clinical integration (e.g., providers communicate the message in routine care), (b) community integration (e.g., organizations promote the message to the public), (c) media coverage and dissemination, and (d) message persistence (e.g., continuous exposure via media outlets). Delivering the message involves the collaboration of many constituents within the community including health care providers, applicable government agencies, community leaders, and media outlets.…”
Section: Nursing Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is found in the Dutch program "Healthy School Approach" (Pucher et al 2015), where physicians take on coordinating roles between the different sectors in public health services that have clear management structures. In regard to (2), a community-based program to prevent prenatal mercury poisoning was developed in a US study (Callejo and Geer 2012). In this case, physicians imparted specific health information to their patients during routine appointments.…”
Section: Introductionmentioning
confidence: 99%